Essays on applied microeconomics - BARBOSA, Antonio Vinícius Barros (2018)
This thesis is composed by three unrelated chapters in applied microeconomics. In the first chapter I estimate the effect of hosting the Summer Olympic Games on country’s subsequent sports performance. In the second chapter I use the flash flood that occurred in the Brazilian state of Santa Catarina in 2008 to estimate the existence of spatial spillovers from natural disasters in geographically linked areas. The final chapter tests the “mobile guardianship” hypothesis on criminal activity through a quasi-experiment caused by the introduction of the ninth digit in mobile phones in some municipalities of the Brazilian state of São Paulo. The first chapter examines the effect of hosting the Summer Olympic Games on future country’s sport success, computing the total number of Olympic medals in the subsequent Games. In order to control for the endogeneity produced by the hosting decision, we use the Synthetic Control Method (SCM), which constructs a weighted country that works as a synthetic counterfactual. The main finding of this paper is that, although decreasing over time, the ex-host effect does not fade away immediately after hosting for some host countries (as Australia and Canada), and that the effect is negligible for middle income countries (as Mexico and Greece). Despite the high costs associated with hosting mega-events such as the Olympic Games, the results shed some light on an important benefit generated from investments in sports. In the second chapter I use a flash flood that occurred in the Brazilian state of Santa Catarina in 2008 to investigate the existence of spatial spillovers from natural disasters in geographically linked areas. For that, I estimate a difference-in-differences model that explicitly allows for the existence of spatial interactions within affected and non-affected regions. The results show that municipalities directly affected by the flood suffered a 8.47% decrease in GDP per capita on the year of the disaster. Three years after the flood however GDP per capita rebounded back to pre-disaster levels in all sectors but the Agricultural sector. Finally, the spatial estimations show that spillovers exist and are economically relevant. The final chapter presents prelimary evidence on how cell phone technology shocks affects crimes. If the phone guardianship hypothesis for crime drop is true, one should expect that exogenous shocks in mobile technology have impact on crime. The present study tests the discontinuity in the number of mobile access and its effects on a range of crimes and on victimization. Using data from Secretaria Estadual de Segurança Pública de São Paulo (SSP) and Brazilian Ministry of Health I estimate the average effect through a temporal difference-in-differences. The results suggest that the ninth digit have a significant impact on homicides and bodily injury, but no effect on vehicle and property thefts. The results provide an insight into the relationship between mobile technology and crime, in addition to supporting the expansion of technology-based policies to deter crime.